Milk-Based Extraction Technology Enhances the Bioavailability and Anti-inflammatory Activity of Ginger Extract - Zhen MA; Jun XU; Juan WU; Caiyun WANG; Jian HE; Pu JING (Shipin gongye ke-ji, 2024)
This study was conducted to evaluate the bioavailability and anti-inflammatory efficacy of ginger milk extract through cell and animal experiments compared with commercial ginger water extract. High-performance liquid chromatography was used to analyze the contents of ginger phenols in ginger extract. The bioavailability of ginger milk extract in Caco-2 model and its effect on ulcerative colitis in rats were evaluated. The results showed that the content of 6-gingerol, the active component in ginger, was increased by 13.1% in ginger milk extract than that in the water extract. The total phenols in ginger milk extract were more easily absorbed by Caco-2 cells than that in the water extract, increasing by 34.9% after 24 hours of culture. Compared with ginger water extract, ginger milk extract significantly reduced the decline of body mass, DAI score, alleviate colon atropymass, and spleen index of colitis rats. The expression level of TNF-α, IL-1β, IL-6 in colon tissue significantly decreased (P<0.05). The activity of superoxide dismutase (SOD) was increased, and the content of malondialdehyde (MDA) was significantly decreased (P<0.05). The results showed that ginger milk extract showed better bioavailability and effectively relieve the symptoms of ulcerative colitis in rats induced by sodium glucan sulfate. The experimental results could provide theoretical reference for the efficient extraction of ginger active ingredients and the development of functional food.